ETV6-NTRK3 positive mammary analogue secretory carcinoma of the salivary gland: a case report and literature review - Yuan, Yachen; Zhao, Lixian; Pan, Yun; Gao, Bo (Journal of the Pakistan Medical Association, 2025)
Mammary analogue secretory carcinoma (MASC) of the salivary gland is an extremely rare salivary gland tumour. It shows the same morphological, immunohistochemical and molecular features as that of the secretory carcinoma of the breast, making it a diagnostic enigma. Here, we report a case of ETS variant transcription factor 6 (ETV6)—neurotrophic receptor tyrosine kinase 3 (NTRK3) fusion gene positive MASC. A 59-year-old woman presented to our hospital with a mass on the right cheek. Computed tomography (CT) showed a nodular shadow in the right mandibular region, and the post-operative pathological diagnosis was confirmed as MASC (pT1N0M0). Immunohistochemical staining showed that the tumour cells were positive for pan-TRK, mammaglobin, and S-100. Fluorescence in situ hybridisation (FISH) confirmed the diagnosis. ETV6 gene translocation and ETV6-NTRK3 gene fusion, but MET gene translocation was negative. Immunohistochemistry and genetic analysis are important tools to differentiate MASC from its morphological mimickers. The treatment approach for MASC has not been well defined or standardised, necessitating further studies to develop evidence-based guidelines. Keywords: Salivary glands, Mammary analogue secretory carcinoma, ETV6-NTRK3 fusion.